Influence of potassium hydroxide and method of carbonization treatment in garden and corn waste microwave pyrolysis. (November 2018) - Grycova, B.; Pryszcz, A.; Lestinsky, P.; Chamradova, K.
Abstract: After initial selection, the samples of garden and corn waste were activated by potassium hydroxide and processed by microwave pyrolysis using both single-step and double-step methods. Experiments were carried out in a self-made microwave reactor for 20 min at the power of 440 W. The distribution and quality of the resulting products were evaluated. The gaseous components were analysed discontinuously by gas chromatography. The concentration of measured hydrogen (activated corn waste 54.4 vol %, non-activated corn waste 18.8 vol %) was strongly influenced by activation and material selection. The char with a heating value of 33.3 MJ kg −1 suggested the direction of its further use as fuel. Optimum conditions of sorbents production from garden waste material with a surface area of 530 m 2 g −1 with regard to the influence of the activation were determined. Graphical abstract: Highlights: The garden waste was thermal treated in the microwave reactor. The KOH activation affected the distribution of final products. Maximum BET surface area of 530.3 m 2 g −1 was observed.